Implementasi Metode Shuhulah dalam Meningkatkan Akhlakul Karimah Pada Anak Usia Dini di Rumah Tahfiz Jami’ul Huda Sumatera - Tegar Digjayadi; Mutiara Fauza Maharani Harahap; Elfina Dwi Lestari; Satria Wiguna (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to examine the role of Al-Qur'an memorisation in improving the morals of students at Rumah Tahfiz Jami'ul Huda Sumatra. The research method used is descriptive qualitative with an analytical approach. This research explores the meaning and perspective of the subject to provide an overview of the research setting and discussion of the results. Rumah Tahfiz Jami'ul Huda Sumatera was established in 2017 with the aim of teaching the knowledge of the Qur'an and improving the morals of students. This research involved interviews with the leadership and teaching staff at the tahfiz house. The results showed that Rumah Tahfiz Jami'ul Huda Sumatera plays a significant role in improving the morals of students through the teaching method of the Qur'an and akhlakul karimah. The teaching method applied is the shuhulah method, which makes it easier for students to memorise the Qur'an by introducing the Latin writing of the Qur'an before mastering tajweed. However, there are obstacles in the application of discipline, habituation of akhlakul karimah, and limited facilities. Other obstacles include the lack of parental role in supporting children's learning process and excessive use of mobile phones. This study concludes that the role of Qur'an memorisers is very important in improving the morals of students, and the shuhulah method is proven to be effective in facilitating the memorisation process for early childhood. The speaker hopes that this method can be used as a learning capital in various other tahfiz houses.